Bibliometric Analysis of Learning Organization - Geok, Soh Wan; Ali, Mohamad Bin Bilal (The journal of contemporary issues in business and government, 2021)
Having the consideration of learning is a continuous effort put into the development of human capital and talent development for organizations of all kinds, scholarly interest in learning organization has consistently increased in the past decade due to its potential to create and disseminate valuable knowledge to enhance innovative performance and sustainable organizations. Knowing the increasing research in this field, this article analyzes and reports on various types of published works related to learning organizations. This study adopted a bibliometric analysis based on the data obtained from Scopus database as at date 24 January 2021. Keywords through search string are utilised for the search results and found 1,671 valid documents for further analysis. Authors have employed VOSviewer for data visualization purpose, Harzing Publish Or Perish and R for standard bibliometric indicators, particularly on the growth rate of publications, analysis of the citation, and research productivity. Findings revealed analysis of document type, source type, top language used, subject area, research trend, top countries, top influential institutions, most productive authors, most active source, top keywords used, and citation analysis. As this study is only using one of the major databases, Scopus, hence, there is a limitation in the search results. Another limitation is in the case where authors are having few registrations in the same database which will affect the accuracy of the productivity in authorship and affiliation details. In this paper, we identify future research directions and future research agenda in learning organization.